Managing Road Risk: The Development of Road Infrastructure Toward Liveable City - Abd Rahim, Mohd Hilmi Izwan; Mohd Zuhori, Farhan Hakimi; Zainal, Rozlin (Journal of Techno-Social, 2024)
A country's economic development and prosperity depend on its cities. This study is conducted due to the an effectiveness of road infrastructure are still a key issue that affecting quality of life in urban areas. Traffic jams, accidents and delays not only cause driver frustration and inconvenience, but also have serious economic and environmental impacts. This study attempts to identify the type of road infrastructure, to investigate the risk classification of road infrastructure and to suggest the potential development of road infrastructure in development of rural area. The study focused on the rural development area and this research includes data collection from primary and secondary sources such as interviews. Stakeholders and expert players has been interviewed for this research. The data that we found has been analysis using content analysis which is matrix table. The results of this study have found that there are several issues that exist in implementing of good road infrastructure concept and initiatives and development in rural development area. In conclusion, all respondents gave a positive review on the study and the research shows that good road infrastructure is needed to create our country safer and our cities towards liveable city.